Heinrich Heine Dichter und Jurist in Göttingen - Lipp, Volker; Möllers, Christoph; Pfordten, Dietmar von der (Universitätsverlag Göttingen, 2007)
This collection gathers the lectures, held at the colloquium of the faculty of law of the University of Goettingen in 2006, the official "Heinejahr".